(untitled) (Journal of Information Technologies in Education (ITE), 2008)
This article deals with the introduction of new information technologies in educational process and new approaches to effective use of ICT in education. We consider the concept of component-oriented approach, its features and scope. We consider the structure of modern pedagogical software tools, briefly considered the appointment of each of the modules. We consider one of modern approaches to filling the content of courses.